The effect of value add tax on economic growth and its sources in developing countries - Kolahi, Seyed Hossein Ghaffarian; Mohd Noor, Zaleha (Canadian Center of Science and Education, 2016)
Today the role of economic growth for its effect on social welfare is undeniable. For this reason, the factors influencing the economic growth are taken into account by policy makers and researchers. On the other hand, the VAT has been considered by most of the countries due to its numerous advantages and benefits. Hence, investigating how this type of tax affects the economic growth seems to be indispensable, particularly in developing countries. In this study, the effect of value added tax on economic growth was examined especially on the developing countries. In details, the effects of VAT on the economic growth of 19 developing countries for duration of 1995 to 2010 were investigated. For analysing the data, the GMM panel was employed because of the structure of the model. Afterwards, the effect of VAT through the channel of saving on the capital accumulation and productivity and ultimately the economic growth was examined. The results revealed that VAT has a negative effect on capital accumulation growth in the level; the positive effect of VAT on the level of economic growth seems to have been imposed through channels other than the increase of saving and its effect on capital accumulation.